India's Approach to Open Banking : Some Implications for Financial Inclusion - Carriere-Swallow, Yan.; Haksar, Vikram; Patnam, Manasa (Washington, D.C. : International Monetary Fund, 2021)
We examine how the development of the digital infrastructure known as the 'India Stack'-including an interoperable payments system, a universal digital ID, and other features-is delivering on the government's objective to expand the provision of financial services. While each individual component of the India Stack is important, we argue that its key overarching feature is a foundational approach of providing extensive public infrastructures and standards that generates important synergies across the layers of the Stack. Until recently, a large share of India's population lacked access to formal banking services and was largely reliant on cash for financial transactions. The expansion of mobile-based financial services that enable simple and convenient ways to save and conduct financial transactions has provided a novel alternative for expanding the financial net. The Stack's improved digital infrastructures have already allowed for a rapid increase in the use of digital payments and the entry of a range of competitors including fintech and bigtech firms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet